Comprehensive analysis of cucumber RAV family genes and functional characterization of CsRAV1 in salt and ABA tolerance in cucumber - Li, Jialin; Song, Chunying; Li, Hongmei; Wang, Siqi; Hu, Linyue; Yin, Yanlei; Wang, Zenghui; He, Wenxing (Frontiers in Plant Science, 2023)
The RAV (related to ABI3 and VP1) transcription factors are specific and exist in plants, which contain a B3 DNA binding domain and/or an APETALA2 (AP2) DNA binding domain. RAVs have been extensively studied in plants, and more and more evidences show that RAVs are involved in various aspects of plant growth and development, stress resistance and hormone signal transduction. However, the systematic analysis of RAV family in cucumber is rarely reported. In this study, eight CsRAV genes were identified in cucumber genome and we further comprehensively analyzed their protein physicochemical properties, conserved domains, gene structure and phylogenetic relationships. The synteny analysis and gene duplications of CsRAV genes were also analysed. Cis-element analysis revealed that the CsRAVs promoter contained several elements related to plant hormones and abiotic stress. Expression analysis showed that NaCl and ABA could significantly induce CsRAV genes expression. Subcellular localization revealed that all CsRAVs were localized in the nucleus. In addition, 35S:CsRAV1 transgenic Arabidopsis and cucumber seedlings enhanced NaCl and ABA tolerance, revealing CsRAV1 may be an important regulator of abiotic stress response. In conclusion, comprehensive analysis of CsRAVs would provide certain reference for understanding the evolution and function of the CsRAV genes.